2017
DOI: 10.3389/fncel.2017.00331
|View full text |Cite
|
Sign up to set email alerts
|

Partial Aminoglycoside Lesions in Vestibular Epithelia Reveal Broad Sensory Dysfunction Associated with Modest Hair Cell Loss and Afferent Calyx Retraction

Abstract: Although the effects of aminoglycoside antibiotics on hair cells have been investigated for decades, their influences on the dendrites of primary afferent neurons have not been widely studied. This is undoubtedly due to the difficulty in disassociating pathology to dendritic processes from that resulting from loss of the presynaptic hair cell. This was overcome in the present investigation through development of a preparation using Chinchilla laniger that enabled direct perilymphatic infusion. Through this str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 95 publications
0
16
4
Order By: Relevance
“…These authors used low-dose intra-labyrinth injection of gentamicin in the chinchilla and found that persistent alterations in the calyx afferents occurred together with the continued presence of the corresponding HCs. As the model and methods used by Sultemeier and Hoffman (2017) differ greatly from the ones used here, it is unclear whether the present data and their data reveal similar or distinct phenomena.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…These authors used low-dose intra-labyrinth injection of gentamicin in the chinchilla and found that persistent alterations in the calyx afferents occurred together with the continued presence of the corresponding HCs. As the model and methods used by Sultemeier and Hoffman (2017) differ greatly from the ones used here, it is unclear whether the present data and their data reveal similar or distinct phenomena.…”
Section: Discussionmentioning
confidence: 72%
“…Understanding these processes should allow us to better predict the reversibility of induced functional loss, to identify candidate targets for pharmacological blockade to stop the transition from reversible to irreversible damage, or for ameliorating or accelerating the recovery processes. Traditionally, most studies on ototoxicity have focused on models causing rapid HC degeneration (e.g., Taylor et al, 2008;Li et al, 2011), but the need to understand other consequences of ototoxicity is starting to be appreciated (Hirvonen et al, 2005;Sedó-Cabezón et al, 2014Gaboyard-Niay et al, 2016;Sultemeier and Hoffman, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though viable type I hair cells remained, animals 1 month post gentamicin administration had severe attenuation of stimulus-evoked afferent discharge modulation. However, spontaneous discharge rates were consistent throughout all testing intervals ( 44 ). Hair cell damage caused by frontal blast-wave exposure could be significant enough to cause the vestibular pathologies observed.…”
Section: Discussionmentioning
confidence: 92%
“…Since in mammals, little to no spontaneous hair cell regeneration occurs following loss, it is likely that the stereocilia damage observed following blast in the present findings would remain permanent ( 42 ). For reference, gentamicin-induced hair cell loss in the vestibular cristae through middle ear injections typically does not result in total type I hair cell loss ( 43 , 44 ). Even though viable type I hair cells remained, animals 1 month post gentamicin administration had severe attenuation of stimulus-evoked afferent discharge modulation.…”
Section: Discussionmentioning
confidence: 99%